Kogan Scale - Attitudes toward old people: translation, cross-cultural adaptation and validation in Brazil - Perez, Franciele Costa da Silva [UNESP]; Colichi, Rosana Maria Barreto [UNESP]; Urrutia, Veronica Gomez; Figueroa, Andres Jimenez; Alves, Renata Camargo [UNESP]; Lima, Silvana Andrea Molina [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2024)
Objective: To present the translation, cross-cultural adaptation and validation of the Kogan's Attitude towards Older People Scale (KAOP) into Portuguese in Brazil. Methods: Methodological research into the translation, cross-cultural adaptation and validation of the Kogan scale on attitudes towards the older adult. Following international recommendations, the scale was translated by three native Brazilians and then a single version was drawn up by consensus considering semantic and cultural equivalences; it was back-translated and evaluated by a native British consultant for similarity analysis. The final version was applied to thirty students regularly enrolled in undergraduate courses as a pre-test. To validate the instrument, a cross-sectional study was carried out with 904 undergraduate students, including health courses, and the Cronbach's alpha index was obtained. Results: In 47% (16) of the items there were exact similarities between the translations and in 53% (18) the similarities prevailed in terms of content, with few semantic differences. In relation to the pre-test, the majority of students were aged up to 25 (60%), female (76.6%) and single (70%), reporting adequate understanding of the Portuguese version, with no need for changes. The scale's internal consistency (Cronbach's alpha) was 0.70. Conclusion: The process of translating, cross-culturally adapting and validating the Kogan scale from English into Brazilian Portuguese carefully followed the steps recommended in the literature. The resulting instrument was evaluated as comprehensible and with good internal consistency.
Keywords: Cross-cultural comparison; Attitude; Perception; Aging; Validation studies